2017
DOI: 10.1038/s41467-017-00285-1
|View full text |Cite
|
Sign up to set email alerts
|

Measuring inter-protein pairwise interaction energies from a single native mass spectrum by double-mutant cycle analysis

Abstract: The strength and specificity of protein complex formation is crucial for most life processes and is determined by interactions between residues in the binding partners. Double-mutant cycle analysis provides a strategy for studying the energetic coupling between amino acids at the interfaces of such complexes. Here we show that these pairwise interaction energies can be determined from a single high-resolution native mass spectrum by measuring the intensities of the complexes formed by the two wild-type protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 18 publications
4
30
0
Order By: Relevance
“…5; Fersht et al, 1992). Double mutant cycle analysis has been widely used to measure the strengths of intramolecular and intermolecular side-chain interactions for both globular and membrane proteins (Serrano et al, 1990, 1991; Doura and Fleming, 2004; Hong et al, 2006, 2007; Harel et al, 2007; Joh et al, 2008; Sokolovski et al, 2017). To minimize the possibility of creating new interactions after mutation, we replaced each active site residue with alanine (Horovitz, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…5; Fersht et al, 1992). Double mutant cycle analysis has been widely used to measure the strengths of intramolecular and intermolecular side-chain interactions for both globular and membrane proteins (Serrano et al, 1990, 1991; Doura and Fleming, 2004; Hong et al, 2006, 2007; Harel et al, 2007; Joh et al, 2008; Sokolovski et al, 2017). To minimize the possibility of creating new interactions after mutation, we replaced each active site residue with alanine (Horovitz, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…A very interesting application of double mutant cycles has been recently implemented by studying the formation of protein-protein interactions via native mass spectrometry [ 51 ]. The intrinsic power of this technique lies in the ability to transfer protein complexes to the gas phase, without altering their native state [ 52 , 53 , 54 ].…”
Section: Double Mutant Cycles By Native Mass Spectrometrymentioning
confidence: 99%
“…Double mutant cycles by mass spectrometry have been successfully employed to study the binding between the proteins E9 and Im2 [ 51 ] and, more recently, to understand the dimerization of SOD1 in naturally-occurring mutants associated with ALS. The authors analyzed the coupling constants by co-expressing wild-type SOD1 with ALS-causing mutations [ 57 ].…”
Section: Double Mutant Cycles By Native Mass Spectrometrymentioning
confidence: 99%
“… 81 An earlier study has shown that pairwise interaction energies can be determined from a single mass spectrum. 82 On the basis of this understanding, four different proteins, consisting of the two wild type (wt) and two mutated (mut) variants, were coexpressed in the same bacterial cells. 21 The spectrum measured from the crude lysate showed the four coexisting complexes (wt/wt, wt/mut, mut/wt, and mut/mut), from which the coupling energy was calculated, obviating the need to purify each of the four proteins and determine individual binding constants for each of the generated dimers.…”
Section: Direct Msmentioning
confidence: 99%